Implementing polymeric pseudorotaxanes for boosting corneal permeability and antiaspergillus activity of tolnaftate: formulation development, statistical optimization, ex vivo permeation and in vivo assessment - Diana Aziz; Sally Mohamed; Saadia Tayel; Amal Makhlouf (Taylor & Francis Group, 2022)
Fungal keratitis (FK) is a devastating ocular disease that can cause corneal opacity and blindness if not treated effectively. Tolnaftate (TOL) is a selective fungicidal drug against Aspergillus spp. which are among the most common causes of mycotic keratitis. TOL is lipophilic drug with low water solubility and permeation which act as obstacles for its clinical ocular efficacy. Hence, this study aimed to statistically optimize a novel polymeric pseudorotaxanes (PSRs) containing TOL for enhancing its ocular permeability and antifungal effect. For achieving this goal, a full 31.22 factorial design was fashioned for preparing and optimizing TOL-PSRs using film hydration technique. Three formulation variables were studied: drug amount (X1), weight ratio of Pluronics to HPβCD (X2) and Pluronic system (X3). Entrapment efficiency percent (EE%) (Y1), particle size (PS) (Y2) and zeta potential (ZP) (Y3) were set as dependent variables. The selected optimal TOL-PSRs (PSR1) showed EE% of 71.55 ± 2.90%, PS of 237.05 ± 12.80 nm and ZP of −32.65 ± 0.92 mV. In addition, PSR1 was compared to conventional polymeric mixed micelles (PMMs) and both carriers significantly increased the drug flux and resulted in higher amount permeated per unit area in 8 h compared to drug suspension. The histopathological studies assured the safety of PSR1 for ocular use. The in vivo susceptibility testing using Aspergillus niger confirmed that PSR1 displayed sustained antifungal activity up to 24 h. The obtained results revealed the admirable potential of PSR1 to be used as novel nanocarriers for promoting TOL ocular delivery.